Human rights in Southeast Asia: Optimism despite teething troubles - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The movement to advance human rights in Southeast Asia has been an uphill climb for activists, particularly in countries that do not recognise this to be of fundamental importance. However, there are signs that the region is warming up to such ideals, along with the rest of the world. Speaking at a Wee Kim Wee Lunchtime Seminar, prominent Singapore human rights activist Braema Mathi offers some reasons for optimism.